Properties of an Extracellular Protease of Bacillus megaterium DSM 319 as Depilating Aid of Hides - BUDIASIH WAHYUNTARI; HENDRAWATI HENDRAWATI (Microbiology Indonesia, 2012)
Properties of a Bacillus megaterium DSM319 extracellular protease which are related to its application for depilating hides were investigated. The properties observed were optimum temperature and pH, the type of protease, and type of the protein which could be hydrolyzed by the enzyme. The enzyme was produced in a 3.5 liters LKB jar fermentor in a medium containing (2.0% v v-1 molasses and 1.3% w v-1 urea at 37 ºC , pH 7.5, aeration 1 vvm, agitation 250 rpm for 24 hours). The enzyme solution was concentrated by means of membrane ultrafiltration followed by ammonium sulfate precipitation at 70% w v-1 saturation. Optimal temperature and pH were observed at 30 ºC and pH 8 respectively. Two mM PMSF and EDTA inhibited the enzyme leaving level of activity of 84.5 and 4.3% correspondingly, indicated that the crude enzyme might be a metal requiring serine protease. The presence of 0.5, 2.0, and 3.5 mM CaCl caused an increase of the enzyme activity of 73, 88, and 79% respectively. The enzyme was able to hydrolyze Na-Benzoyl-DL-Arginine p-Nitro Anilide, a specific amino acid sequence cleaved by trypsin at a reaction rate of 0.024 absorbance value at 405 nm per minute. The enzyme was capable of hydrolyzing bovine serum albumin, hemoglobin, and gelatin, and to hydrolyze alkaline soluble collagen and keratin. The K value of the enzyme for hydrolysis of bovine serum albumin and gelatin was 3.44 m and 1.65 mg mL-1, whereas V values were 8.09 and 55.24 mg mL-1 respectively. The experimental data showed max that the crude enzymes have potential for dehairing of cowhides.